Interaksi Sosial Umat Islam-Hindu Di Magersari Desa Tarokan Kecamatan Tarokan Kabupaten Kediri - Muarofah, Selfi Sinta; Asy'ari, Asy'ari (Satya Widya: Jurnal Studi Agama, 2023)
This article will discuss the interaction of Muslims and Hindus in Magersari Hamlet in Tarokan Village and District, Kediri Regency. This study used qualitative research methods. The purpose of this research is first, to find out the patterns of social-religious interaction; The second is to find out the factors that influence the interaction between the two religions. Based on the results of the study, the pattern of social interaction between Muslims and Hindus in Magersari Hamlet, Tarokan Village is associative and leads to cooperation, accommodation, and assimilation in the daily lives of Muslims and Hindus. Harmony, assimilation, and social capital are patterns of social interaction that exist for Muslims and Hindus. Social space to recognize human activity itself because of the activities of others. Muslims and Hindus engage in regular, harmonious and conflict-free social interactions in various economic, social and religious endeavors, thereby generating this meaning. The social interaction of Muslims and Hindus in Magersari Hamlet, Tarokan Village is influenced by various factors, including the attitude of residents who help each other and work together.